2020
DOI: 10.1097/txd.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for GTKO/β4GalNT2KO Pigs as the Preferred Organ-source for Old World Nonhuman Primates as a Preclinical Model of Xenotransplantation

Abstract: Background. Triple-knockout (TKO) pigs (in which expression of the 3 known pig carbohydrate xenoantigens has been deleted) are likely to be an optimal source of organs for transplantation into human recipients, many of whom do not have natural antibodies against TKO pig cells. However, old world monkeys, for example, baboons, have natural antibodies directed to TKO cells (to a “fourth” xenoantigen that is exposed after TKO). Methods. We measured (1) ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 17 publications
5
40
0
Order By: Relevance
“…In our experience, we have rarely identified baboons in which this was the case, although sometimes antibody binding to the two pig cell types is comparable. However, antibody binding to TKO pig cells is associated with a very high degree of cytotoxicity 5,6 . These observations indicate that it will be difficult to identify baboons with lower antibody binding to TKO pig cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experience, we have rarely identified baboons in which this was the case, although sometimes antibody binding to the two pig cell types is comparable. However, antibody binding to TKO pig cells is associated with a very high degree of cytotoxicity 5,6 . These observations indicate that it will be difficult to identify baboons with lower antibody binding to TKO pig cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that it will be difficult to identify baboons with lower antibody binding to TKO pig cells. We have therefore suggested that a different pig (ie, a GTKO/β4GalNT2KO) is required for studies in baboons than those that will be ideal for clinical trials (ie, a TKO) 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that TKO pigs could be ideal sources of organs for future clinical xenotransplantation, 10 but they are less suitable for preclinical studies in non‐human primate models 8‐11 . Differences in immune reactivity to CMAHKO pigs (including TKO) between baboons and humans might contribute to variations in the results 9,11 . In baboons, sensitization to TKO pig cells is probably, at least in part, to the 4th xenoantigen (a carbohydrate) exposed after CMAHKO.…”
Section: Discussionmentioning
confidence: 99%
“…Although A3GALT2 KO pigs rarely had an effect on pig-to-human immune reactivity in our study, it could provide more information on the role of iGb3 on NKT cell activity in preclinical test. Recently, preclinical studies have reported that pigs with a CMAH gene knocked out express new xenoantigens called ''forth xenoantigen'' in pig-to-Old World NHP organ transplantation (Cooper et al 2020;Cui et al 2020;Yamamoto et al 2020). This finding indicates that it is, as yet, almost impossible to confirm the effect of CMAH KO in preclinical tests.…”
Section: Discussionmentioning
confidence: 99%